Determination of Recurrence, Severity, Distress, and Clustering of Symptoms in the Elderly with Colorectal Cancer in Selected Hospitals in Isfahan - Iran in 2018 to 2019 - Arghavan Esmaeili; Parvaneh Khorasani; Masoud Bahrami; Habibollah Hosseini (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Colorectal cancer (CRC) is one of the most common and age-related cancers worldwide. Objectives: The present study aimed to determine the recurrence, severity, distress, and clustering of symptoms in the elderly with colorectal cancer in the selected hospitals in Isfahan from 2018 to 2019. Methods: This descriptive-analytical study was conducted over a period of six months on 300 patients with colorectal cancer in selected hospitals in Isfahan. Data collection tools were contextual questionnaires and symptom recall scale (MSAS). To determine the correlation matrix between symptoms (clusters), a heuristic analysis factor was used in terms of mean recurrence, severity, and distress of symptoms in research units through PCA heuristic analytical method in SPSS 16. Results: The most common symptoms in terms of recurrence were dry mouth (32.92%) and numbness and frisson (24.55%). The most common symptoms in terms of recurrence were dry mouth (80.33%) and nausea (86%); the most common symptoms in terms of severity were dry mouth (41%) and nausea (29.8%). The most common signs of distress were "I do not look like myself" (6) and dry mouth (35.3%). Finally, five clusters were obtained, including systemic, psychiatric, cardiovascular, mucosal, and gastrointestinal symptoms. Conclusion: The results of the present study showed that psychological symptoms had a higher percentage of recurrence, severity, and distress in CRC patients than physical symptoms.